Từ giả thiết suy ra:
\(\left(x+y\right)\left(x^2-xy+y^2\right)+2\left(x^2-xy+y^2\right)+\left(x^2+2xy+y^2\right)+4\left(x+y\right)+4=0\)
\(\Leftrightarrow\left(x^2-xy+y^2\right)\left(x+y+2\right)+\left(x+y+2\right)^2=0\)
\(\Leftrightarrow\dfrac{1}{2}\left(x+y+2\right)\left(2x^2+2y^2-2xy+2x+2y+4\right)=0\)
\(\Leftrightarrow\dfrac{1}{2}\left(x+y+2\right)\left[\left(x-y\right)^2+\left(x+1\right)^2+\left(y+1\right)^2+2\right]=0\)
\(\Rightarrow x+y=-2\)
Mà xy>0 nên x,y cùng nhỏ hơn 0
Áp dụng AM-GM,ta có: \(\sqrt{\left(-x\right)\left(-y\right)}\le\dfrac{-x-y}{2}=1\)
\(\Rightarrow xy\le1\Rightarrow\dfrac{-2}{xy}\le-2\)
\(\dfrac{1}{x}+\dfrac{1}{y}=\dfrac{x+y}{xy}=\dfrac{-2}{xy}\le-2\)